2015
DOI: 10.1021/acs.analchem.5b01409
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Mapping of Sulfated Glycotopes by Negative Ion Mode nanoLC–MS/MS-Based Sulfoglycomic Analysis of Permethylated Glycans

Abstract: We have previously developed the enabling techniques for sulfoglycomics based on mass spectrometry (MS) analysis of permethylated glycans, which preserves the attractive features of more reliable MS/MS sequencing compared with that performed on native glycans, while providing an easy way to separate and hence enrich the sulfated glycans. Unlike LC-MS/MS analysis of native glycans in negative ion mode that has been more widely in use, the characteristics and potential benefits of similar applications based on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…We have previously shown that by converting all hydroxyl groups including the carboxylic groups of sialic acids into O-methyl, permethylation allows simple enrichment and identification of a wealth of sulfated glycans occurring at low abundance that would otherwise not be detected (7,8). We further demonstrated that negative ion mode nanoLC-MS/MS can be productively applied in acidic buffer commonly used in proteomics without compromising much the stability and detection sensitivity (9). Low mass MS 2 diagnostic ions for locating the sulfate onto the common Gal␤1-3/4GlcNAc unit, with and without additional sialylation, were identified and we suggested that ambiguity in assignment can conceivably be addressed by additional MS 3 mode that will not suffer from low mass cutoff the way an ion trap based fragmentation would (9).…”
Section: Brain the Complexity Of Their Terminal Glycotopes Includingmentioning
confidence: 91%
See 2 more Smart Citations
“…We have previously shown that by converting all hydroxyl groups including the carboxylic groups of sialic acids into O-methyl, permethylation allows simple enrichment and identification of a wealth of sulfated glycans occurring at low abundance that would otherwise not be detected (7,8). We further demonstrated that negative ion mode nanoLC-MS/MS can be productively applied in acidic buffer commonly used in proteomics without compromising much the stability and detection sensitivity (9). Low mass MS 2 diagnostic ions for locating the sulfate onto the common Gal␤1-3/4GlcNAc unit, with and without additional sialylation, were identified and we suggested that ambiguity in assignment can conceivably be addressed by additional MS 3 mode that will not suffer from low mass cutoff the way an ion trap based fragmentation would (9).…”
Section: Brain the Complexity Of Their Terminal Glycotopes Includingmentioning
confidence: 91%
“…We further demonstrated that negative ion mode nanoLC-MS/MS can be productively applied in acidic buffer commonly used in proteomics without compromising much the stability and detection sensitivity (9). Low mass MS 2 diagnostic ions for locating the sulfate onto the common Gal␤1-3/4GlcNAc unit, with and without additional sialylation, were identified and we suggested that ambiguity in assignment can conceivably be addressed by additional MS 3 mode that will not suffer from low mass cutoff the way an ion trap based fragmentation would (9).…”
Section: Brain the Complexity Of Their Terminal Glycotopes Includingmentioning
confidence: 93%
See 1 more Smart Citation
“…To account for the observed sulfoglycomic differences contributed by different GlcNAc6STs, the nanoLC-MS/MS spectra for the few major monosulfated O-glycans commonly found in the parental SW480 and all three transfected cell lines were extracted and manually interpreted to delineate their isomeric structures and location of sulfate based on detecting a combination of previously reported diagnostic ions (38,40,41). In the case of m/z 1025, 1386, and 1474, which seemingly defined the most obvious differences in the MS profiles of monosulfated O-glycans made by cells overexpressing the three GlcNAc6STs ( Fig.…”
Section: Identification Of Monosulfated O-glycan Structuresmentioning
confidence: 99%
“…applied to more problematic glycans, such as the sulfated glycans and/or to derive linkage-specific information requiring advanced MS/MS. Over the last few years, we have steadily established a reasonably robust and sensitive sulfoglycomic platform based initially on MALDI-MS/MS and then nanoLC-MS/MS analyses of permethylated sulfated glycans fractionated away from the otherwise dominant nonsulfated components (36,40,41,45,46). These technical advances now enable us to meaningfully dissect the in vivo specificities of various GlcNAc6STs on O-glycans by sulfoglycomic analysis that focused on a few representative base structures, with a good balance of precision and sensitivity.…”
Section: Substrate Specificities Of Human Glcnac6stsmentioning
confidence: 99%